2017
DOI: 10.9738/intsurg-d-15-00172.1
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Hashimoto's Thyroiditis of the Thyroid Gland

Abstract: Immunoglobulin (Ig) G4-related Hashimoto's thyroiditis is a newly discovered subtype of Hashimoto's thyroiditis and characterized by thyroid inflammation and marked fibrosis. IgG4-related Hashimoto's thyroiditis is very rare and there has been relatively little information available to date. A 46-year-old woman with a past history of thyroid dysfunction visited our outpatient clinic for severe anterior neck swelling. She complained of swallowing discomfort and pain due to severe goiter and was successfully tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Our patient's symptoms due to mass effect (dysphagia, airway obstruction) rather than chemical insult (eg, heat or cold intolerance, tremors, changes in energy level, etc.) align with reports of Luiz et al, 14 Kang et al, 16 and Zhao et al 18 in which neck swelling without symptoms of thyroid dysfunction were observed. Indeed, Li et al 1 found 39% (11/28) of IgG4-RHT cases to be associated with subclinical hypothyroidism.…”
Section: Clinical Featuressupporting
confidence: 92%
“…Our patient's symptoms due to mass effect (dysphagia, airway obstruction) rather than chemical insult (eg, heat or cold intolerance, tremors, changes in energy level, etc.) align with reports of Luiz et al, 14 Kang et al, 16 and Zhao et al 18 in which neck swelling without symptoms of thyroid dysfunction were observed. Indeed, Li et al 1 found 39% (11/28) of IgG4-RHT cases to be associated with subclinical hypothyroidism.…”
Section: Clinical Featuressupporting
confidence: 92%